Skeletonized internal thoracic artery is associated with lower rates of mediastinitis in elderly undergoing coronary artery bypass grafting surgery Artéria torácica interna esqueletizada está associada a menores taxas de mediastinite em idosos submetidos à cirurgia de revascularização miocárdica - Michel Pompeu Barros de Oliveira Sá (Brazilian Journal of Cardiovascular Surgery, 2011)
BACKGROUND AND OBJECTIVES: Mediastinitis is a serious complication of median sternotomy and is associated to significant morbidity and mortality. The aim of this study is to identify which option of harvesting internal thoracic artery (ITA), pedicled or skeletonized, is associated with lower rates of mediastinitis after coronary artery bypass grafting surgery (CABG) in elderly, in the Division of Cardiovascular Surgery of PROCAPE. METHODS: Retrospective study of 160 elderly who underwent consecutive CABG between May 2007 and June 2011. Eleven preoperative variables, four intraoperative variables and eight postoperative variables possibly involved in the development of postoperative mediastinitis were evaluated between two groups: CABG with skeletonized ITA (n=80) and pedicled ITA (n=80). Univariate and multivariate logistic regression analyses were applied. RESULTS: The incidence of mediastinitis was 6.8% (n=11), with a lethality rate of 54.5% (n=6). The skeletonized ITA group were more exposed than pedicled ITA group to obesity (n=12 vs. n=4; 15% vs. 5%; P=0.035) and multiple transfusions (n=25 vs. n=11; 31.2% vs. 13.7%; P=0.008). The pedicled ITA group presented a greater risk of mediastinitis after CABG than skeletonized ITA group (n=10 vs. n=1; 12.5% vs. 1.2%; Unadjusted OR 11.3; 95% CI 1.4 - 241.5; P=0.008). In multivariate analysis, this difference maintained statistically significant (Adjusted OR 5.2; 95% CI 1.5-495.8; P=0.012), being considered an independent association. CONCLUSIONS: We suggest that elderly should be considered for strategies to minimize risk of infection. In elderly that undergo unilateral ITA, the problem seems to be related to how ITA is harvested. Elderly should always be considered for use of skeletonized ITA. JUSTIFICATIVA E OBJETIVOS: Mediastinite é séria complicação da esternotomia mediana e está associada a significativa morbidade e mortalidade. O objetivo deste estudo é identificar qual técnica de obtenção da artéria torácica interna (ATI), dissecção pediculada ou esqueletizada, está associada a menores taxas de mediastinite após cirurgia de revascularização miocárdica (CRM) em idosos, na Divisão de Cirurgia Cardiovascular do PROCAPE. MÉTODOS: Estudo retrospectivo de 160 idosos submetidos consecutivamente à CRM entre maio/2007 e junho/2011. Onze variáveis pré-operatórias, quatro intraoperatórias e oito pós-operatórias, possivelmente envolvidas no desenvolvimento de mediastinite após CRM, foram avaliadas entre dois grupos: CRM com ATI esqueletizada (n=80) e ATI pediculada (n=80). Análises univariada e multivariada por regressão logística foram aplicadas. RESULTADOS: A incidência de mediastinite foi 6,8% (n=11), com taxa de letalidade de 54,5% (n=6). Grupo ATI esqueletizada foi mais exposto à obesidade (n=12 vs. n=4; 15% vs. 5%, P=0,035) e múltiplas transfusões (n=25 vs. n=11; 31,2% vs. 13,7%; P=0,008) do que grupo ATI pediculada. Grupo ATI pediculada apresentou maior risco de mediastinite após CRM que grupo ATI esqueletizada (n=10 vs. n=1; 12,5% vs. 1,2%; OR não-ajustado 11,3; IC 95% 1,4-241,5; P=0,008). Na análise multivariada, esta diferença manteve-se estatisticamente significativa (OR ajustado 5,2; IC 95% 1,5-495,8; P=0,012), sendo considerada uma associação independente. CONCLUSÕES: Sugerimos que os idosos devem ser considerados para estratégias de minimização de risco de infecção. Em idosos submetidos à CRM com ATI unilateral, o problema parece estar relacionado à forma como a ATI é obtida. Idosos devem ser sempre considerados para o uso de ATI esqueletizada.